Money, power, and monetary regimes - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2016)
Money, in this paper, is defined as a power relationship of a specific kind, a stratified social debt relationship, measured in a unit of account determined by some authority. A brief historical examination reveals its evolving nature in the process of social provisioning. Money not only predates markets and real exchange as understood in mainstream economics but also emerges as a social mechanism of distribution, usually by some authority of power (be it an ancient religious authority, a king, a colonial power, a modern nation state, or a monetary union). Money, it can be said, is a 'creature of the state' that has played a key role in the transfer of real resources between parties and the distribution of economic surplus. In modern capitalist economies, the currency is also a simple public monopoly. As long as money has existed, someone has tried to tamper with its value. A history of counterfeiting, as well as that of independence from colonial and economic rule, is another way of telling the history of 'money as a creature of the state.' This historical understanding of the origins and nature of money illuminates the economic possibilities under different institutional monetary arrangements in the modern world. We consider the so-called modern 'sovereign' and 'nonsovereign' monetary regimes (including freely floating currencies, currency pegs, currency boards, dollarized nations, and monetary unions) to examine the available policy space in each case for pursuing domestic policy objectives.
Keywords: B5; E6; E42; E63; F45; N1; Z1; 330; History of Money; Monetary Sovereignty; Chartalism; Counterfeiting; Public Monopoly; Currency Issuers vs. Currency Users; Exchange Rate Systems